Fluorine-Modified Rutaecarpine Exerts Cyclooxygenase-2 Inhibition and Anti-inflammatory Effects in Lungs - Lee, Chiming; Liao, Jiahnhaur; Chen, Seuhwa; Yen, Chiaohan; Lee, Yuchieh; Huang, Shihhao; Huang, Shengtung; Lin, Chunmao; Chang, Vincent Hungshu (Frontiers in Pharmacology, 2019)
Inflammation is the first step that leads to inflammatory cell migration, cytokine release, and myofibroblast formation. Myofibroblasts can deposit excess amounts of extracellular matrix. Cyclooxygenase (COX) inhibitor exhibits strong anti-inflammatory response; however, this is usually achieved with undesirable side effects. In this study, we demonstrated the effects of the fluorine-modified rutaecarpine (RUT), fluoro-2-methoxyrutaecarpine (F-RUT), in inflammatory damage in the lungs. Based on the results, F-RUT retained anti-inflammatory activity both in vitro and in vivo in lungs. Compared to the parent compound, F-RUT showed better COX-2 suppression as a COX-2-selective inhibitor with lower cytotoxicity, and enhanced molecular reactivity and biological activity. F-RUT was also observed to reduce reactive oxygen species (ROS) generation and inflammatory infiltrating neutrophils in lipopolysaccharide (LPS)-stimulated zebrafish and ovalbumin (OVA)/alum-challenged KLF-10-knockout mouse lungs, respectively. Furthermore, F-RUT ameliorated the respiratory function in OVA/alum-challenged BALB/c mice by maintaining the thickness of the blood-air barrier in mouse lungs. Overall, these data suggest that F-RUT may function as an effective therapeutic agent for inflammation-induced lung dysfunction, and a better selection for pharmaceutical purposes than conventionally-used anti-inflammatory agents.